1343 Care-flow connect: 'paper out of pocket campaign' – use of technology to ensure SBAR handover. (17th August 2022) - Low, M; Kumari, D; Effendi, K; Mikhail, M; Dreghici, I; Prathapan, J; Levy, C; Chiesela, S; Rogers, D; Margabanthu, G
Abstract : Aims: Handover has great variability across the teams. Consistency of team handovers with SBAR approach has been well emphasized. Effective handovers relate positively to patient safety. The clear system approach ensures consistency and standard of practice across the teams between change overs to provide seamless excellent patient care. Objective: Our Paediatric team wanted to ensure effective consistent handover with use of technology supported by the trust and join in the 'paper out of pocket' campaign. Methods: Careflow connect was used for handover in March 2020, there were a few engagement sessions introduced to help the team to be trained and engaged in the process. Quality Improvement pillars were used to help the team address barriers of change and effectively embed the change in practice around handovers. (Figure-1 and figure-2) COVID meant that team handovers were individual number restricted in each room to limit exposure. Technology wave at KGH helped explore and embrace the new SBAR approach to app based and white board based systematic handovers in Feb 2021. Results: Effective handovers with social distancing was maintained. It helped maintain closed clear communication loops and minimized error. It offered clarity in the content of information shared consistently across teams. Tertiary care conversations were captured effectively and documented. The process was well embraced with medical teams, 50% nursing staff felt it was easily accessible however some still had a concerns about network connectivity. Paper was out of pocket with handovers. Challenges were the need for training with skill updates, access and connectivity issues and protected time to update handovers. QI process helped raise the awareness within the Team with use of surveys to review practice, to build consistency and share good practice. Conclusion: The Careflow connect process since its introduction with the Covid Technology boom in Healthcare has ensured safe and effective patient care; driven by SBAR based consistent and clear handover process. Introduction of white boards on the ward, since Feb 2021 has helped focus consistency in process and change as a team. Strengthening change was achieved with positive team attitudes, behaviours and engagement. Visibility of QI methods, timely and ease of access to technology was a driving force for effective patient care. Patient safety was positively influenced by effective handover of care processes between teams with paper out of pocket.